Early Return to Work after Carpal Tunnel Release with Ultrasound Guidance - Paul D. Paterson, MD; Matthew J. Kirsch, MD; Larry E. Miller, PhD, PStat; Demetrio J. Aguila, III, MD (Plastic and Reconstructive Surgery, Global Open, 2024)
Background:. The duration of postoperative leave varies by the carpal tunnel release (CTR) technique. This study aimed to determine the time to return to work (RTW) after CTR with ultrasound (CTR-US) guidance and identify factors contributing to this duration. Methods:. This was a multicenter postmarket registry of patients treated with CTR-US. Time to RTW was analyzed with Kaplan–Meier methods. Logistic regression identified the association of patient, work, and procedural factors with the probability of RTW within 5 days (a standard work week) after CTR-US. Results:. A total of 544 employed patients (655 hands) from 24 centers were treated with CTR-US between November 2019 and August 2022. The mean patient age was 50 years, 62% were women, and most (76%) were full-time employees, where work activities were desk-based (49%), light manual (28%), or heavy manual (23%). The complication rate was 0.8%. After CTR-US, the median RTW was 3 days (interquartile range: 1–6 days), with 74.6% returning by 5 days, 87.8% by 10 days, and 97.1% by 30 days. Work activity (desk-based versus heavy manual: odds ratio = 2.93, 95% confidence interval: 1.70–5.04, P < 0.001) and sex (man versus woman: odds ratio = 1.85, 95% confidence interval: 1.15–2.98, P = 0.01) were associated with higher probability of RTW within 5 days. The median RTW ranged from 2 to 4 days in all patient subgroups, including heavy manual laborers (median 4 days) and women (median 3 days). Conclusions:. CTR-US offers an efficient approach to treating CTS, enabling most patients to RTW with minimal delay. The short recovery periods observed across diverse patient and work characteristic subgroups compare favorably to other CTR techniques.